Digitalization of customs procedures in developing countries and its impact on trade flows : сase of Kenia - Didichenko, Vladyslav; Shymanska, Kateryna; Horáková, Ludmila; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis examines how the digitalization of customs procedures affects trade flows in developing countries, using Kenya as a case study. The research aims to assess the impact of customs digitalization on trade facilitation outcomes and to identify key factors that support or constrain the effective deployment of digital solutions. Two research questions guide the analysis: (1) What is the impact of digitalizing customs procedures on trade flows? (2) What major challenges and barriers hinder the full deployment of digital solutions in the customs domain? Methodologically, the thesis combines quantitative and qualitative approaches. A Difference-in-Differences analysis of the World Bank “Trading Across Borders” indicator (2006–2020) compares Kenya with Tanzania and Uganda and shows that, after the introduction of the National Electronic Single Window (Kenya TradeNet) and the Integrated Customs Management System (iCMS), Kenya recorded a significant relative improvement in border-processing efficiency. Complementary case studies of the Regional Electronic Cargo Tracking System, One Stop Border Posts, scanner deployment and the Integrated Scanner Command and Control Centre demonstrate gains in transparency, predictability and risk-based controls along the Northern Corridor. An analysis of trade statistics for 2004–2024 indicates that exports to key partners (Uganda, the Netherlands and Pakistan) became steeper and more stable in the post-digital period, while imports remained high but more volatile, reflecting exposure to global shocks. Digitalization thus emerges as an enabling factor that strengthens the resilience, efficiency and credibility of Kenya’s trade environment rather than an autonomous driver of trade growth.
Remaining constraints include persistent paper-based requirements, uneven infrastructure and connectivity, gaps in digital skills, regional synchronization issues and cybersecurity risks, which inform the strategic policy recommendations formulated in the thesis.
Vedoucí práce: Kateryna Shymanska
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses